Weedy plants at Ugolnye Kopi Village, Anadyrsky District, Chukotka Autonomous Area - E. G. Nikolin (Труды по прикладной ботанике, генетике и селекции, 2024)
The village of Ugolnye Kopi (Anadyrsky District, Chukotka Autonomous Area, Russia) is located in the left-bank estuary part of the Anadyr River, on the shore of the Anadyr Firth, overlooking the Bering Sea. Despite a relatively low latitude (64°44’N), more suitable for the development of boreal vegetation, the effect of cold-sea air masses on the environments of this locality forms vegetation more typical of the Subarctic tundra subzone. Penetration of adventive plant species, human satellites, into this area is very limited. There has been no previous information about the composition of the synanthropic flora at Ugolnye Kopi Village. Some data concerning adventive plants in the vicinity of the town of Anadyr were available in the review published by N. A. Sekretareva and A. A. Korobkov from the Komarov Botanical Institute. A survey conducted in August 2021 resulted in identifying an adventive component of the flora in the vicinity of Ugolnye Kopi, consisting of 44 vascular plant species. A key role in the village’s spontaneous landscaping has been played by 18 species of apophytes that arrived and settled there from the surrounding vegetation. Seven more apophytic species came to the village from more distant places of Chukotka. The usual synanthropic component, long ago acclimatized in Chukotka, is represented by 7 species: Hordeum jubatum, Chenopodium prostratum, Descurainia sophioides, Erysimum boreale, E. cheiranthoides, Taraxacum ceratophorum, and T. officinale s.l. Invasive species alien to this area are Elytrigia repens, Puccinellia borealis, Oberna behen, Stellaria media, Boechera pendula, Capsella bursa-pastoris, Trifolium repens, Lappula anisacantha, L. heteracantha, Lepidotheca suaveolens, Senecio dubitabilis, and S. vulgaris.